SAVINGS AND INCOME RELATIONSHIPS AMONG HOUSEHOLDS: A REVIEW OF THE LITERATURE - DANIEL AIDOO-MENSAH (Agricultural Socio-Economics Journal, 2018)
The paper is a survey of available literature on savings-income functions in developing countries. It gives critical examination of some of the major theories underlying savings and income functions. In doing this, the paper highlighted the concept of savings and some empirical studies done in the area of savings-income relationships and their findings as well as economic implications of the findings. The import of the paper stems from the fact that domestic savings of which household savings is an important component has contributed immensely to the economic transformation of some economies and the determinants of such savings well researched. Hence, understanding the theoretical underpinnings of the savings-income relationships would pave way for further studies to be conducted in Ghana, thereby, replicating such success stories. This is because a better understanding of the savings-income relationship will contribute to the formulation of appropriate policies for savings mobilisation, thereby improving upon local capital formation capacity. Moreover, a good knowledge gained of the savings-income phenomenon particularly at the rural household level in Ghana will give the monetary authorities a fair idea of how the rural economy operates and how to make improvements in this sector to enable its integration into the mainstream financial system.